TEACHING AND LEARNING ACTIVITIES OUTSIDE THE CLASSROOM TO IMPROVE THE QUALITY OF LEARNING FOR STUDENTS - Hidayah, Linta Wafdan (WACANA DIDAKTIKA, 2015)
Teaching and learning can become inherently spontaneous and student-centeredwhen moved from the confines of the classroom into the world at large. From theÂ collaborative learning atmosphere that results from the unique relationships developedÂ outside the classroom, to the deep learning that occurs when students must put intoÂ practice âin the real worldâ what they have theorized about from behind a desk, fieldÂ experiences are unmatched in their learning potential. Field experiences early in aÂ studentâs career can be formative and can inspire students to continue in a field. TheÂ outside the classroom learning experience, commonly known as âfield tripâ, is a type ofÂ experiential learning which get students away from the formal classroom into a newÂ environment. It can as simple as taking the class out on to the campus for a drawingÂ exercise. Outside classroom activities can include summer field camps, extended stays atresearch stations and even a semester abroad.. the potential benefits for teaching andÂ learning outside the classroom activities can be enormous . putting a class into a differentÂ physical setting generates a bond among class members and creates a learning community.Â Sometimes simply getting to the field trip destination is an opportunity for students to getÂ to know each other, as well as their instructor. Active field trips can also offerÂ unprecedented opportunities for experiential learning.